Musical Culture of Podlasie: Change, Transformation, Assimilation - Lukashenko, Larysa (Tautosakos darbai, 2020)
Podlasie is a territory of ethnic borderlands, where the Polish, Ukrainian, and Belarusian cultures have coexisted for centuries. Political conflicts of the last century and deportations during the “Wisla Operation” in 1947 have led to today’s situation where the territories of Northern and Southern Podlasie, which some decades ago featured a unified ethnical dialect, now differ in ethno-cultural terms. In Southern Podlasie, native music culture has partially been recovered by people returning from exile to northern Poland in the 60s and 70s, while Ukrainian musical folklore has almost disappeared. Musical folklore traditions existed in the northern part of Podlasie (which was not touched by the mass transmigration of the mid-1940s) until the end of the twentieth century and continues to exist to a certain extent. This article investigates the dynamics of this transformation in Southern Podlasie through audio recordings and published sourсes. Particular attention is paid to the processes of interpenetration and assimilation of the repertoire of closely co-existing Polish and Ukrainian musical cultures. The final aspect of the study is a comparison of ethnic and cultural processes in Northern and Southern Podlasie.